GC-MS and UHPLC-QTOFMS-assisted identification of the differential metabolites and metabolic pathways in key tissues of Pogostemon cablin - Wang, Xiaobing; Zhong, Liting; Zou, Xuan; Gong, Lizhen; Zhuang, Jiexuan; Zhang, Danhua; Zheng, Hai; Wang, Xiaomin; Wu, Daidi; Zhan, Ruoting; Chen, Likai (Frontiers in Plant Science, 2023)
Pogostemon cablin is an important aromatic medicinal herb widely used in the pharmaceutical and perfume industries. However, our understanding of the phytochemical compounds and metabolites within P. cablin remains limited. To our knowledge, no integrated studies have hitherto been conducted on the metabolites of the aerial parts of P. cablin. In this study, twenty-three volatile compounds from the aerial parts of P. cablin were identified by GC-MS, predominantly sesquiterpenes. Quantitative analysis showed the highest level of patchouli alcohol in leaves (24.89 mg/g), which was 9.12 and 6.69-fold higher than in stems and flowers. UHPLC-QTOFMS was used to analyze the non-volatile compounds of leaf, stem and flower tissues. The differences in metabolites between flower and leaf tissues were the largest. Based on 112, 77 and 83 differential metabolites between flower-leaf, flower-stem and leaf-stem, three tissue-specific biomarkers of metabolites were identified, and the differential metabolites were enriched in several KEGG pathways. Furthermore, labeling differential metabolites in the primary and secondary metabolic pathways showed that flowers accumulated more lipids and amino acids, including proline, lysine and tryptophan; the leaves accumulated higher levels of terpenoids, vitamins and flavonoids, and stems contained higher levels of carbohydrate compounds. Based on the role of acetyl coenzyme A, the distribution and possible exchange mechanism of metabolites in leaves, stems and flowers of P. cablin were mapped for the first time, laying the groundwork for future research on the metabolites in P. cablin and their regulatory role.